Empowering Early Childhood Educators: The Role of Montage in Developing Fine Motor Skills and Creativity - Asmara, Berda; Rulyansah, Afib; Aquariza, Novi Rahmania; Syaikhon, Muhammad; Shari, Destita (UKInstitute, 2024)
This study explores the impact of montage activities on the development of fine motor skills and creativity in early childhood education, as implemented in a community service project at TK Dharma Bhakti Surabaya. The project aimed to train PAUD teachers to integrate montage as a pedagogical tool, fostering both physical and creative growth in children aged 4 to 6. The training provided teachers with hands-on experience in conducting montage activities and assessing student outcomes in these developmental areas. Data were collected through pre- and post-training assessments of both teachers and students. The results showed a significant improvement in teachers’ confidence and competence in using montage for educational purposes. Additionally, students exhibited substantial gains in fine motor skills, with an average improvement of 20% in tasks involving cutting, pasting, and object manipulation. Creativity scores also improved, with 75% of students demonstrating enhanced creative expression through the use of diverse materials and techniques. The findings support the use of montage as an effective strategy for addressing the dual goals of motor skill development and creative thinking in early childhood education. Furthermore, the project highlights the importance of providing teachers with professional development opportunities that focus on creative pedagogies. While challenges such as resource availability and balancing academic content with creative activities were noted, the study offers valuable insights into the practical implementation of art-based learning in resource-constrained settings.